Pengaruh kinerja keuangan, aktivitas pemasaran, dan aset tidak berwujud terhadap nilai perusahaan pada perusahaan manufaktur sektor konsumsi periode 2016-2020 - Khusnul Khotimah, Deva; Nuswandari, Cahyani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of financial performance, marketing activities, and intangible assets on firm value in manufacturing companies in the consumption sector for the period 2016 – 2020. This research is a type of quantitative research with descriptive method. The population in this study are manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange for the period 2016 – 2020. Methods The sampling used was purposive sampling, with data that was processed as many as 88 companies after being outliers from 102 companies. The analytical method used is using multiple regression analysis method. The results showed that liquidity had a negative and insignificant effect on firm value, solvency had a positive and significant effect on firm value, profitability had a positive and significant impact on firm value, and marketing activities had a significant positive effect on firm value. While intangible assets have a negative and insignificant effect on firm value.